Acute Appendicitis in Pregnancy and the Developing World. (20th July 2017) - Bhandari, Tika Ram; Shahi, Sudha; Acharya, Sarita
Abstract : Background . Acute appendicitis is the commonest nonobstetric surgical emergency during pregnancy. The aim of the study was to compare perioperative outcomes of acute appendicitis in pregnant and nonpregnant patients. Methods . A retrospective review of medical records of 56 pregnant patients between 2011 and 2016 who were compared with 164 nonpregnant women of reproductive age who underwent open appendectomy between 2014 and 2016 for acute appendicitis. The patient's demographics and perioperative data were analyzed. Results . The median age of pregnant and nonpregnant patients observed was 26 years (range 19–37) and 26 years (range 18–43). There were no significant differences between the groups in negative appendectomy (21.4 and 21.3%, P = 0.52 ), perforated appendicitis (25 and 23.8%, P = 0.85 ), postoperative complications (28.6 and 26.8%, P = 0.80 ), and median length of hospital stay (5 and 4.5 days, P = 0.36 ). There were 3.6% preterm labour, no maternal mortality, and no fetal loss. In multivariate analysis, WBC >18000/mm 3 and long patient time to surgery were independent risk factors for appendicular perforation and postoperative complication (P < 0.05 ). Conclusion . Our results of appendectomy in pregnant patients are comparable with nonpregnant patients. Hence the same perioperative treatment protocol can be followed in pregnant and nonpregnant patients even in resource-poor setting.